Politik Identitas dalam Teks Sastrawan Bali - Darma Putra, I Nyoman (Jurnal Kajian Bali (Journal of Bali Studies), 2011)
Abstract This article examines short stories and novels by Balinese writers that depictmeetings, friendships and love affairs between Balinese and Western characters.The works discussed were written either in the national or the Balinese languageand were published between the 1960s and 2000s, coinciding with the developmentof mass tourism in Bali. One distinctive feature of the works is that narrators avoidmixed marriages between Balinese and Westerners despite the love between them.This recurrent theme goes against reality in which mixed marriage is common andaccepted in the Balinese community. During the period in which these works werepublished, the discourse on Balinese cultural identity has been very important andhighly debated in the mass media against the backdrop of the tourism industryand its potential negative impacts. This article argues that Balinese writers useliterary works to articulate their opinion about the importance of Balinese peoplemaintaining their Balineseness or cultural identity. Their works are meaningfulwhen viewed as an expression of Balinese identity politics in facing what isconsidered to be the growing threat of tourism.
Keywords: Bali, Balinese writers, Balinese cultural identity, politics of representation